German Registry for Cardiac Operations and Interventions in Patients with Congenital Heart Disease: Report 2021 and 9 Years' Longitudinal Observations on Fallot and Coarctation Patients - Dittrich, Sven; Arenz, Claudia; Krogmann, Otto; Tengler, Anja; Meyer, Renate; Bauer, Ulrike; Hofbeck, Michael; Beckmann, Andreas; Horke, Alexander (The Thoracic and Cardiovascular Surgeon, 2022)
Background The annual report of the German Quality Assurance of Congenital Heart Disease displays a broad overview on outcome of interventional and surgical treatment with respect to patient's age and risk categorization. Particular features of the German all-comers registry are the inclusion of all interventional and surgical procedures, the possibility to record repeated treatments with distinct individual patient assignment, and to record various procedures within one case.Methods International Pediatric and Congenital Cardiac Code terminology for diagnoses and procedures as well as classified adverse events, also recording of demographic data, key procedural performance indicators, and key quality indicators (mortality, adverse event rates). Surgical and interventional adverse events were classified according to the Society of Thoracic Surgeons and to the Congenital Heart Disease Adjustment for Risk Method of the congenital cardiac catheterization project on outcomes. Annual analysis of all cases and additional long-term evaluation of patients after repair of Fallot and primary treatment of native coarctation of the aorta were performed.Results In 2020, 5,532 patients with 6,051 cases (hospital stays) with 6,986 procedures were treated in 23 German institutions. Cases dispense on 618 newborns (10.2%), 1,532 infants (25.3%), 3,077 children (50.9%), and 824 adults (13.6%). Freedom from adverse events was 94.5% in 2,795 interventional cases, 67.9% in 2,887 surgical cases, and 42.9% in 336 cases with multiple procedures (without considering the 33 hybrid interventions). In-hospital mortality was 0.5% in interventional, 1.6% in surgical, and 5.7% in cases with multiple treatments. Long-term observation of 1,632 patient after repair of Fallot depicts the impact of previous palliation in 18% of the patients on the rate of 20.8% redo cases. Differentiated analysis of 1,864 patients with native coarctation picture clear differences of patient, age, and procedure selection and outcome. The overall redo procedure rate in this patient population is high with 30.8%.Conclusion Improvement in quality of care requires detailed analysis of risks, performance indicators, and outcomes. The high necessity of redo procedures in patients with complex congenital heart disease underlines the imperative need of long-term observations.
Keywords: congenital heart disease; outcomes; multicenter registry; risk categorization; pediatric cardiology; congenital heart surgery; transcatheter intervention; Fallot; coarctation